ULTRA-LOW TEMPERATURE KINETICS OF NEUTRAL-NEUTRAL REACTIONS - NEW EXPERIMENTAL AND THEORETICAL RESULTS FOR OH+HBR BETWEEN 295-K AND 23-K - Sims, I; Smith, I; Clary, D; Bocherel, P; Rowe, B (1994)
The first determination of the rate of reaction of OH radicals with HBr at temperatures below 249 K is reported. Rate constants measured from 295 to 23 K increase monotonically with decrease in temperature and are faster than has previously been thought at the temperatures present in the mid and low stratosphere. The observed negative temperature dependence is well predicted by a simple formula deduced from quantum scattering calculations employing the rotating bond approximation. © 1994 American Institute of Physics.